JAZ proteins: Key regulators of plant growth and stress response - Xiaoqian Zhao; Yongqi He; Yuxin Liu; Zhoufei Wang; Jia Zhao (Crop Journal)
The jasmonate ZIM-domain (JAZ) family of proteins serves as co-receptors and transcriptional repressors of jasmonic acid (JA) in plants. Their functional diversity and multiple roles make them important components of the regulatory network of JA and other hormonal signaling pathways. In this review, we provide an overview of the latest findings on JAZ family proteins and emphasize their roles in plant growth and development, and response to biotic and abiotic stress, along with their underlying mechanisms. Moreover, existing challenges and future applications are outlined with the aim of offering a reference for further research on JAZ proteins in the context of plant physiology.